Chlorinated Paraffins - Boer, Jacob; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Chlorinated paraffins are one of the last classes of chlorinated compounds that are still being produced worldwide and used in high quantities in many applications. They are particularly used in cutting oils in the metal industry, but also as lubricants, plasticizers, flame retardants and as additives in adhesives, rubber, paints and sealants. This volume covers the state-of-the-art of methods for the synthesis and analysis of chlorinated paraffins. Experts in the field provide an overview of their worldwide occurrence and utilization and describe their toxicological properties. International regulations and production volumes are presented as well as an example of a risk assessment study that was carried out in Japan. This book is a valuable and comprehensive source of information for environmental scientists interested in the occurrence and toxicology of chlorinated paraffins and for authorities and producers.
Short-Chain Chlorinated Paraffins: Production, Use and International Regulations -- Synthesis of Polychloroalkanes -- Analysis of Chlorinated Paraffins in Environmental Matrices: The Ultimate Challenge for the Analytical Chemist -- Environmental Levels and Fate -- Overview of the Mammalian and Environmental Toxicity of Chlorinated Paraffins -- Risk Assessment of Short-Chain Chlorinated Paraffins in Japan.
Keywords: Environmental sciences; Analytical biochemistry; Geochemistry; Environmental chemistry; Environment; Environmental Chemistry; Geochemistry; Analytical Chemistry